Occupational exposure to Aflatoxin B1 in a Portuguese poultry slaughterhouse - Viegas, Susana (2016)
Aflatoxin B1 (AFB1) is a secondary metabolite produced by the fungi Aspergillus flavus and is the most potent hepatocarcinogen known in mammals and has been classified by the International Agency of Research on Cancer as Group 1 carcinogen. Although dietary exposure to AFB1 has been extensively documented, there are still few studies dedicated to the problem of occupational exposure. Considering recent findings regarding AFB1 occupational exposure in poultry production, it was considered relevant to clarify if there is also exposure in poultry slaughterhouses. Occupational exposure assessment to AFB1 was done with a biomarker of internal dose that measures AFB1 in the serum by enzyme-linked immunosorbent assay. Thirty workers from a slaughterhouse were enrolled in this study. A control group (n = 30) was also considered in order to know AFB1 background levels for Portuguese population. Fourteen workers (47.0%) showed detectable levels of AFB1 with values from 1.06 to 4.03ng ml(-1), with a mean value of 1.73ng ml(-1). No AFB1 was detected in serum of individuals used as controls. Despite uncertainties regarding the exposure route that is contributing more to exposure (inhalation or dermal) is possible to state that exposure to AFB1 is occurring in the slaughterhouse studied. It seems that reducing AFB1 contamination in poultry production can have a positive result in this occupational setting.